PENERAPAN VALUE OF FAMILY BUSINESS DALAM INTERNAL CONTROL PADA SISTEM PENJUALAN NON BUMN DENGAN PENDEKATAN COSO - Mario Jehezkiel (Jurnal Investasi Islam, 2017)
The development of steel industry in Indonesia shows a fairly rapid growth through consumption increase of 8.3% from 2007 to 2015. PT. BS is a family business in Surabaya which is engaged in steel industry. The problem faced by PT.BS is the flow of funds within the company that is hampered. In addition, there are several other issues that are the high value of bad debts, the payment period of receivables is longer than the standard limits of the company and not found Standard Operational Procedure (SOP) for the bill with the installment payment system. Internal control with COSO approach through value of family business is a strategy designed to improve internal control on the sales system. This researchuses qualitative exploratory method to analyze and evaluate internal control that has been applied by company. The results showed that internal control through the value of family business applied by the company still has many weaknesses in every procedure in the sales system. Therefore, PT.BS needs to apply the value of family bussines in internal control through a non-BUMN sales system with COSO approach to solve all problems and further research on Point of Sales (POS) and Sales Order (SO) necessary.